Controle de temperatura e nível de um tanque por método preditivo - Piechontcoski, Fabiano (2022)
In this work the temperature and level control of a tank, present in a laboratory scale physical plant, was performed using the Model Predictive Control. For this, a plant was assembled with tank and water cooling systems. To implement the control by the proposed method a Python code was used, using a computer to process the information in real time and a microcontroller to change the system controls. Finally, the best conditions found by simulation were applied to the real system, which was able to respond to setpoint changes and in the presence of disturbances.